Pengaruh E – Wom Terhadap Consumer Decision Memilih PT. Permodalan Nasional Madani (PERSERO) Syariah Cabang Kota Bengkulu Dengan Brand Trust Sebagai Variabel Intervening - Anisah Jayanti; Eka Sri Wahyuni; Evan Stiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
A study entitled "Effects of EWOM on Consumer Decisions to Choose PT.Permodanlan Nasional Madani (Persero) Syariah Bengkulu City Branch Brand Trust as an intervening variable has the purposes of, firstly Analyzing Impact of eWom on shoppers Decisions, secondly. knowing the impact of E-Wom on brand trust, thirdly Analyzing impact of brand trust on buyer choice. This study is part of research included in the Expanatory Research Study category using a quantitative descriptive approach in research, analyzed through structural Equation Modeling which is processed using the software application version 20 analysis of moment structure. The sampling technique by purposive sampling is a method sampling through certain criteria and substituting objects in the study. For respondents, there were 136 people who were used as samples. After testing, the findings of the first research E-wom have an important influence on consumer decision and the probability value is 0.000 and the CR is 3,903, both E-wom are proven to have an important influence on brand trust, the probability value is 0.000 and the CR is 4.172, the three Trus Brands have an influence important in consumer decisions, the probability value obtained is 0.033 and the CR is 2.132.